The effect of education and telemonitoring intervention on acute events of patients with heart failure: secondary analysis of the MEETinCY study - Alexandrou, Anna (Department of Nursing, Faculty of Health Sciences, Cyprus University of Technology, 2020)
Background Despite advances in the treatment of heart failure (HF), decompensated HF is characterized by high hospital readmissions and linked with increased morbidity and mortality. Early recognition of deterioration of the symptoms by the patients is vital for reducing acute events and hospital length of stay. Aim This study aimed to determine the effectiveness of a nurse-led management program on the reduction of the number of visits to ER, unplanned readmissions and mortality of patients with HF due to acute events of decompensation at 90- and 180-days post-discharge. The secondary aim was to identify a possible association between demographic or clinical characteristics and the hazard for acute events. Methods This study was designed as a multicenter single-blinded randomized clinical trial (RCT) with three different intervention groups (IGs) and one control group (CG) that received the usual care which did not include a structured educational program. It is part of the study MEETinCY and data were collected from the five big general hospitals of the country. The first IG received only education (EE) before discharge, the second IG received only telephone follow-up (TT) for 90 days after discharge, the third IG included a combination of education before discharge and telephone follow-up (ET) for 90 days months after discharge. The efficacy of interventions on mortality and rehospitalization rates were estimated using a Kaplan Meier analysis and were compared with log rank test. The association of demographic and clinical characteristics to the hazard for acute events was explored using a multivariate Cox regression. The significance testing was based on p value <0.05. Results Two hundred and forty-two (242) patients completed the study [(CC) n=68, (EE) n=57, (ET) n=59, (TT) n=58]. Mean age of patients was 69.5 (SD = 11.5), 64% were male, with NYHA function I-IV but most patients (39.3%) were categorized in NYHA II. During the 90 and 180 days study periods, the intervention groups, although appearing to have a "better survival experience" than the Control group, no statistically significant difference was found between the four groups for the periods 90 (log-rank test, x2 = 3.7 p = 0.28) and 180 (log rang x2=2.87, p=0.41) days.
Keywords: Heart failure; Readmissions; Acute events; Case management program; Nurseled